The semantics of Chinese music : analysing selected Chinese musical concepts - Tien, Adrian (Cognitive linguistic studies in cultural contexts, 2015)
Music is a widely enjoyed human experience. It is, therefore, natural that we have wanted to describe, document, analyse and, somehow, grasp it in language. This book surveys a representative selection of musical concepts in Chinese language, i.e. words that describe, or refer to, aspects of Chinese music. Important as these musical concepts are in the language, they have been in wide circulation since ancient times without being subjected to any serious semantic analysis. The current study is the first known attempt at analysing these Chinese musical concepts linguistically, adopting the Natural Semantic Metalanguage (NSM) approach to formulate semantically and cognitively rigorous explications. Readers will be able to better understand not only these musical concepts but also significant aspects of the Chinese culture which many of these musical concepts represent. This volume contributes to the fields of cognitive linguistics, semantics, music, musicology and Chinese studies, offering readers a fresh account of Chinese ways of thinking, not least Chinese ways of viewing or appreciating music. Ultimately, this study represents trailblazing research on the relationship between language, culture and cognition.